2018
DOI: 10.5194/tc-12-3827-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the current Antarctic surface mass balance to sea surface conditions using MAR

Abstract: Abstract. Estimates for the recent period and projections of the Antarctic surface mass balance (SMB) often rely on high-resolution polar-oriented regional climate models (RCMs). However, RCMs require large-scale boundary forcing fields prescribed by reanalyses or general circulation models (GCMs). Since the recent variability of sea surface conditions (SSCs, namely sea ice concentration, SIC, and sea surface temperature, SST) over the Southern Ocean is not reproduced by most GCMs from the 5th phase of the Cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 60 publications
2
77
1
Order By: Relevance
“…On the other hand, a large majority (80 %) of the profiles showing saturation at each measurement level is associated with the occurrence of drifting snow, the rest of them being most likely linked to the prolonged presence of a saturated environment during calm conditions after the cessation of drifting snow events and/or to maritime air intrusions during cyclonic disturbances (e.g., Gallée, 1996;Kittel et al, 2018). Considering that surface 140 sublimation is less effective at raising the moisture content of the near-surface air than windborne-snow sublimation because of enhanced particle ventilation in drift conditions, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a large majority (80 %) of the profiles showing saturation at each measurement level is associated with the occurrence of drifting snow, the rest of them being most likely linked to the prolonged presence of a saturated environment during calm conditions after the cessation of drifting snow events and/or to maritime air intrusions during cyclonic disturbances (e.g., Gallée, 1996;Kittel et al, 2018). Considering that surface 140 sublimation is less effective at raising the moisture content of the near-surface air than windborne-snow sublimation because of enhanced particle ventilation in drift conditions, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we propose that the rate of surface water needed to saturate the firn and lead to hydrofracturing has to increase by a factor of 2.5 to 40 depending on the ice shelf. Such an increase could be reached under strong warming scenarios given the exponential temperature dependence described by Trusel et al (2015), although snowfall is also expected to increase (Krinner et al, 2008;Agosta et al, 2013;Ligtenberg et al, 2013;Lenaerts et al, 2016;Palerme et al, 2017), requiring even more meltwater to reach saturation. In their projections, Kuipers Munneke et al (2014) found that the western part of Abbot as well as Cosgrove could become watersaturated before the end of the twenty-second century, but the other ice shelves of the Amundsen sector remained nonsaturated.…”
Section: Discussionmentioning
confidence: 99%
“…The CMIP5 ensemble was reduced to 21 members because we discarded models sharing the same history of development and high code comparability. The model list is the same as in Krinner and Flanner (2018) and can be seen in the Fig. 1 legend.…”
Section: Sea Surface Conditions In Cmip5 Aogcmsmentioning
confidence: 99%
“…While performing a limited number of climate projections, we cover a large range of the uncertainties associated with the evolution of the Southern Ocean surface condition for the Antarctic climate because it was shown to be its primary driver (Krinner et al, 2014). This approach is supported by the fact that biases of large-scale atmospheric circulation of coupled climate models were shown to be highly stationary under strong climate change (Krinner and Flanner, 2018) and that the response of the ARPEGE atmospheric model to the introduction of the same SSC "bias" was shown to be mostly unchanged in future climate. The use of stretched-grid AGCMs and polar-oriented RCMs to downscale future climate projections for Antarctica comports their own assets and drawbacks, and rather than opposed, they could be combined as for Africa in Hernández-Díaz et al (2017).…”
Section: Implication Of Sea Surface Condition Selectionmentioning
confidence: 99%